Indoleamine 2, 3 Dioxygenase 1 Impairs Chondrogenic Differentiation of Mesenchymal Stem Cells in the Joint of Osteoarthritis Mice Model - Alahdal, Murad; Huang, Rongxiang; Duan, Li; Zhiqin, Deng; Hongwei, Ouyang; Li, Wencui; Wang, Daping (Frontiers in Immunology, 2021)
Osteoarthritis (OA) is a serious joint inflammation that leads to cartilage degeneration and joint dysfunction. Mesenchymal stem cells (MSCs) are used as a cell-based therapy that showed promising results in promoting cartilage repair. However, recent studies and clinical trials explored unsatisfied outcomes because of slow chondrogenic differentiation and increased calcification without clear reasons. Here, we report that the overexpression of indoleamine 2,3 dioxygenase 1 (IDO1) in the synovial fluid of OA patients impairs chondrogenic differentiation of MSCs in the joint of the OA mice model. The effect of MSCs mixed with IDO1 inhibitor on the cartilage regeneration was tested compared to MSCs mixed with IDO1 in the OA animal model. Further, the mechanism exploring the effect of IDO1 on chondrogenic differentiation was investigated. Subsequently, miRNA transcriptome sequencing was performed for MSCs cocultured with IDO1 and then TargetScan was used to verify the target of miR-122-5p in the SF-MSCs. Interestingly, we found that MSCs mixed with IDO1 inhibitor showed a significant performance to promote cartilage regeneration in the OA animal model, while MSCs mixed with IDO1 failed to stimulate cartilage regeneration. Importantly, the overexpression of IDO1 showed significant inhibition to Sox9 and Collagen type II (COL2A1) through activating the expression of β-catenin, since inhibiting of IDO1 significantly promoted chondrogenic signalling of MSCs (Sox9, COL2A1, Aggrecan). Further, miRNA transcriptome sequencing of SF-MSCs that treated with IDO1 showed significant downregulation of miR-122-5p which perfectly targets Wnt1. The expression of Wnt1 was noticed high when IDO1 was overexpressed. In summary, our results suggest that IDO1 overexpression in the synovial fluid of OA patients impairs chondrogenic differentiation of MSCs and cartilage regeneration through downregulation of miR-122-5p that activates the Wnt1/ β-catenin pathway.